Jurnal Penyuluhan: persepsi pemuda terhadap peranan karang taruna dalam peanganan masalah sosial - Annisa Yulia Handayani, Ninuk Purnaningsih (PPs ILMU PENYULUHAN PEMBANGUNAN IPB, 2015)
The government should work with the elements of society to solve a growing social problem, including organizations that exist at the village level. Karang Taruna as one of the youth organizations, is a partner that could take the role in solving social problems.